Studi potensi wisata situs bersejarah di Kabupaten Tulungagung - Triani, Anggi; Yusiana, Lury Sevita; Bawono, Rochtri Agung (Jurnal Arsitektur Lansekap; Vol.8, No.2, Oktober 2022DO - 10.24843/JAL.2022.v08.i02.p07, 2022)
Tulungagung Regency is located near Mojokerto Regency which is the center of the Majapahit Kingdom. This makes it a historical heritage with very diverse historical values. There are six historical sites and one historical museum located in the southern mountainous area of ??Tulungagung Regency. The lack of visits and acts of vandalism by tourists are the problems faced here. Tourist attraction is the potential that drives the presence of tourists to a tourist destination. For this reason, it is necessary to conduct a study on the potential of historical tourism which consists of historical aspects and aspects of tourist attraction of each historical tourism unit, so that it can be used to attract tourist visits and increase awareness of preservation of the historic tourism unit. The stages of this research study are the preparation, inventory, analysis, and synthesis stages. The method of data collection was done through field observations, interviews, and literature studies. The results of this research study the assessment of tourist attractions and the value of the feasibility index. The advice given is a recommendation for a development program for historic tourism units which are considered to be lacking.